Greening the Workforce: Collaborative Curriculum Design for the Sustainable Economy in Post-Pandemic Southeast Asia - Angelica Ronron; Herlan (International Journal For Advanced Research, 2026)
The transition toward a sustainable economy has increased the demand for a workforce equipped with green competencies and the ability to adapt to rapidly changing labor market requirements. This study examined the role of collaborative curriculum design in enhancing green skills development and workforce readiness for a sustainable economy in post-pandemic Southeast Asia. A quantitative research approach was employed using a survey of 312 final-year students and recent graduates from higher education institutions across the region. Data were analyzed using Partial Least Squares Structural Equation Modeling. The findings revealed that collaborative curriculum design contributed significantly to the development of green skills and workforce readiness. Green skills also enhanced workforce readiness and served as an important mechanism through which curriculum collaboration improved graduates’ preparedness for sustainable employment. The results highlighted the importance of collaboration among universities, industry, and other stakeholders in aligning educational outcomes with the competency requirements of the green economy. This study contributed to the literature on sustainability education by demonstrating the strategic role of collaborative curriculum practices in workforce development. The findings suggested that higher education institutions should strengthen sustainability-oriented learning and industry engagement to better prepare graduates for future economic and environmental challenges.